Allostatic Load Is Linked to Cortical Thickness Changes Depending on Body-Weight Status - Ottino-González, Jonatan; Jurado, María A.; García-García, Isabel; Segura, Bàrbara; Marqués-Iturria, Idoia; Sender-Palacios, María J.; Tor, Encarnació; Prats-Soteras, Xavier; Caldú, Xavier; Junqué, Carme; Garolera, Maite (Frontiers in Human Neuroscience, 2017)
Objective: Overweight (body mass index or BMI ≥ 25 kg/m2) and stress interact with each other in complex ways. Overweight promotes chronic low-inflammation states, while stress is known to mediate caloric intake. Both conditions are linked to several avoidable health problems and to cognitive decline, brain atrophy and dementia. Since it was proposed as a framework for the onset of mental illness, the allostatic load model has received increasing attention. Although changes in health and cognition related to overweight and stress are well documented separately, the association between allostatic load and brain integrity has not been addressed in depth, especially among overweight subjects. Method: Thirty-four healthy overweight-to-obese and 29 lean adults underwent blood testing, neuropsychological examination and magnetic resonance imaging to assess the relationship between cortical thickness and allostatic load, represented as an index of 15 biomarkers (this is, systolic and diastolic arterial tension, glycated hemoglobin, glucose, creatinine, total cholesterol, HDL and LDL cholesterol, triglycerides, c-reactive protein, interleukin-6, insulin, cortisol, fibrinogen and leptin). Results: Allostatic load indexes showed widespread positive and negative significant correlations (p < 0.01) with cortical thickness values depending on body-weight status. Conclusion: The increase of allostatic load is linked to changes in the gray matter composition of regions monitoring behavior, sensory-reward processing and general cognitive function.